Proceedings of the SIGDIAL 2009 Conference on the 10th Annual Meeting of the Special Interest Group on Discourse and Dialogue - 2009
DOI: 10.3115/1708376.1708408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of conversational agents on human communication in thought-evoking multi-party dialogues

Abstract: This paper presents an experimental study that analyzes how conversational agents activate human communication in thought-evoking multi-party dialogues between multi-users and multi-agents. A thought-evoking dialogue, which is a kind of interaction in which agents act on user willingness to provoke user thinking, has the potential to stimulate multi-party interaction. In this paper, we focus on quiz-style multi-party dialogues between two users and two agents as an example of a thought-evoking multi-party dial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…Similarly, self-disclosure increased when users had positive preferences for discussion topics and the system's agreement was effective for inducing agreement from users. A study focused on linguistic behavior, i.e., empathic and self-oriented emotional expression in a text-based game-setup, had similar results [26]. In particular, empathic expression significantly improved user satisfaction, raised ratings of a peer agent and increased the number of user utterances emitted in the game.…”
Section: Relevant Researchmentioning
confidence: 76%
“…Similarly, self-disclosure increased when users had positive preferences for discussion topics and the system's agreement was effective for inducing agreement from users. A study focused on linguistic behavior, i.e., empathic and self-oriented emotional expression in a text-based game-setup, had similar results [26]. In particular, empathic expression significantly improved user satisfaction, raised ratings of a peer agent and increased the number of user utterances emitted in the game.…”
Section: Relevant Researchmentioning
confidence: 76%
“…Dohsaka et al (2009) developed a thought-evoking dialogue system for multiparty conversations with a quiz-game task. They reported that the existence of agents and empathic expressions is effective for user satisfaction and can increase the number of user utterances.…”
Section: Introductionmentioning
confidence: 99%
“…Our prior work [Kumar et al 2010a;Kumar et al 2007a] has shown that social behavior motivated from empirical research in small group communication [Bales 1950] can help in effectively supporting students in collaborative learning settings. The use of social interaction in other applications of CAs besides education has been investigated [Bickmore et al 2009;Dybala et al 2009;Dohsaka et al 2009], and in this article, we also demonstrate generality of positive effect from the collaborative learning domain to a collaborative decision-making task. The experiments presented here bridge these two tracks of research, specifically proposing a solution to the challenge of timing social behavior in the context of supporting collaborative learning.…”
Section: Discussionmentioning
confidence: 55%
“…Work in the area of affective computing and its application to tutorial dialog has focused on identification of student's emotional states [D'Mello et al 2008] and using those to improve choice of task-related behavior by tutors. However, recently CAs have been used to support multiparty activities such as collaborative learning [Kumar et al 2007b], communication [Isbell et al 2001], information assistance [Zheng et al 2005;Bohus and Horvitz 2009], and games [Dohsaka et al 2009]. Specifically in the application area of collaborative learning, systematic evaluations of the use of CAs to support small groups of students have shown improvements of more than a letter grade in learning attributed to the support offered by these automated agents [Kumar et al 2007b].…”
Section: Introductionmentioning
confidence: 98%